Inherent safety assessment and consequence analysis of the Liquefied Natural Gas (LNG) Mixed Fluid Cascade (MFC) processes - Masoumeh Narimani; Soroush Baradaran; Mohammad Amin Sobati (Case Studies in Chemical and Environmental Engineering)
This study aims to evaluate the process safety aspects of four types of mixed fluid cascade (MFC) routes commonly used in the LNG liquefaction process. The investigation was conducted based on the conceptual design data using the Comprehensive Inherent Safety Index (CISI) followed by the consequence modeling. The CISI approach provided the path to identify each process vulnerabilities as well as attaining the total safety score for each. According to the outcomes, the two-cycle MFC-2 was the best option while the three cycle MFC-4 that is a latest developed technology with a total score of 351.282 placed in second standings. From another point of view the main common contributor of process incidents were recognized as multi-stream heat exchanger and compressors. Potential major accident hazard modeling associated with the vulnerabilities introduced by CISI analysis also revealed a credible jet fire subsequent to loss of containment from MFC-4 process can introduce a 21.8 m radius for the fire zone boundary. The outcomes of this research would be beneficial for the technology developers as well as engineering designers of LNG facilities since more complicated process safety challenges with end up in extensive requirement for layers of protection.